Printed Chalcogenide/Metal Heterostructured Photodetectors for Flexible Near‐Infrared Sensing. Issue 13 (15th April 2022) - Wang, Jianyang; Pan, Qi; Xie, Hongfei; Ma, Ying; Su, Meng; Chen, Binda; Wang, Huadong; Xue, Tangyue; Zhang, Zeying; Chi, Jimei; Li, Siyi; Song, Yanlin
Abstract: Near‐infrared (NIR) photodetectors can be fabricated for various applications, such as imaging, military tracking, and medical diagnosis. However, achieving miniaturization and high responsivity for NIR photodetector arrays is still a challenge. In this study, a high‐density NIR photodetector array with a micro/nano chalcogenide and silver nanoparticle heterostructure is achieved using a low‐cost printing strategy. The Ag/Ge2 Sb2 Te5 (GST)/Ag heterostructure is fabricated using a template‐assisted sequential printing strategy. At an absorption wavelength of λ = 980 nm, the NIR photodetector has a high light responsivity of 6.7 × 10 4 A W −1 owing to the high crystallinity of the GST microwire and refined GST/Ag heterointerface during the printing process. In addition, the sensing pixel interval can be reduced to 25 µm, corresponding to the highest resolution of NIR photodetectors achieved thus far (resolution: 1.0 × 10 3 dpi). In addition, the NIR photodetector printed on soft substrates exhibits flexibility. Thus, a simple and effective strategy for the fabrication of NIR photodetectors is demonstrated, and precise flexible infrared sensing is achieved. Abstract : A sequential printing strategy was demonstrated for fabricating flexible near‐infrared (NIR) photodetector arrays with refined heterostructures. The photodetector array achieves high density (resolution: 1.0 × 10 3 dpi) and high photoresponse (Detectivity: 3.18 × 10 11 Jones, Responsivity: 6700 A W −1 ) under bending, which makes NIR imaging possible in real time. A general strategy for fabricating integrated electronics and optics is achieved.